Feminine nouns used in the works of Sheikh Muhammad al-Khal and Ibn al-Hajib al-Kurdi: A comparative analytical study - أكريكر, أ.د. عبد المنعم محمد; مصطفى, م.د. محمد أحمد; Amin, L. Diari Abdullah Muhammad (Sulaimani Journal for Humanities, 2023)
Since the dawn of Islam, illuminated by the light of the Quran and enlightened by the laws of the faith, the Kurdish people have brought forth for all humanity the benefits of knowledge and its practitioners. Those across the globe, from east to west, have benefited from their contributions, particularly in the fields of linguistics and legal reasoning, including the various branches of linguistics such as grammar, morphology, lexicography, etymology, syntax, and analogy. Our scholars have recognized that mastery of the language is the sole gateway to understanding Islamic law and being guided by its light. Among the prominent Kurdish scholars who served the language in later times was Sheikh Muhammad al-Khal, a marvel of his era for his unique linguistic research, including his study of feminine nouns derived from oral tradition. He believed that the issue of feminine nouns derived from oral tradition required further investigation, analysis, and examination, and that their precise definition would greatly benefit the language and its foundations. He reasoned that oral tradition is the basis of analogy, giving rise to numerous branches based on oral principles. This, in turn, expands the understanding of the language, corrects what is thought to be erroneous, and refutes what is thought to be correct. Sheikh al-Khal also recognized that the efforts of The previous scholars, though commendable in their field, needed further compilation, follow-up, correction, strengthening, and preference. Therefore, he authored and compiled a concise, unique, and beneficial treatise on the issue of feminine nouns derived from hearing. He was preceded in this field by another Kurdish scholar whose fame spread far and wide: Sheikh Jamal al-Din Ibn al-Hajib, author of distinguished linguistic works that are considered cornerstones of linguistic research in his time and beyond. He had also compiled works on the same subject, namely, feminine nouns derived from hearing. This research necessitated examining the work of the scholar Ibn al-Hajib and comparing it with the work of Sheikh Muhammad al-Khal through comparative inductive study in order to identify points of agreement and disagreement, and the impact of their work on the established principles of feminine nouns derived from hearing.
Keywords: The auditory feminine; Ibn alHajib; Khal; Kurdish; the feminization